Pengaruh Disiplin Kerja, Motivasi Kerja Dan Pengembangan Karir Terhadap Peningkatan Kinerja Pegawai - Yasokhi Hia; Siti Zahara Lubis; Ghozali Ghozali; Didik Opralisda Butar-Butar; Aida Oktafina Saragih; Eddi Suprayitno (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This research aims to find out the influence jointly or partially between work discipline, work motivation and career development to the performance of the Workers at the Dinas Pendidikan Provinsi Sumatera Utara. This research uses descriptive qualitative method using primary and secondary data. The population is the workers of the company. Sixty three workers become the sample of this research. Data analysis technique used is linear regression which shows that from the three independent variables applied to the regression model (work discipline, work motivation and career development). Work discipline is significant for 0,002 which can be concluded that work discipline affects performance (hypothesis 1 accepted). Work motivation has significant value 0,122 which can be concluded that work motivation not affects performance (hypothesis 2 rejected). Career development variable has significant value 0,020 which means that career development influences performance (hypothesis 3 accepted). Research results show that work discipline, work motivation and career development all positively influence the performance of the workers. It can be proven using the result of regression statistic test with probability value 0,000 obtained which is lower than α (α=0,05). So, it can be said that work discipline, work motivation and career development influence positively the performance of the workers. Thus, hypothesis 4 accepted.